Os sentidos do envelhecimento: mulheres transexuais e travestis na cidade de Sorocaba-SP - Corrêa, Sarah Pedro (2024)
The presented dissertation aimed to analyze the meaning of aging in the life story narratives of transsexual and transvestite women residing in the city of Sorocaba, in the interior of the state of São Paulo. Specifically, the study sought to understand how these women construct their self-image, taking the aging process as a turning point, identifying and understanding, in their narratives, the systematic strategies for overcoming the conditions of violence and social and institutional exclusion to which they have been/are subjected. The research adopted Oral History as a theoretical-methodological approach, focusing on the memories and experiences of transsexual and transvestite women. Four transsexual and transvestite women over 35 years old, residing in the city of Sorocaba-SP, were interviewed. In conclusion, the study highlights the presence of adversities and challenges faced by these women, emphasizing, at the same time, the importance of public policies and measures that ensure the full exercise of their rights throughout their lives, specifically in old age.